Kwaresma ang kultura ng pagsamba - Cultural Center of the Philippines (Manila The Center, 1988)
A documentary on the Lenten practices in the Philippines.
VHS.
Keywords: Jesus Christ -- Passion; Holy week -- Philippines; Lent -- Philippines; Philippine history